Sex differences in the association between cognitive function and 24-hour activity patterns in older adults: a compositional data analysis - Li, Dan; Zhou, Mi; Song, Xiaomei (Frontiers in Aging, 2025)
BackgroundCognitive decline is prevalent among older adults and may be associated with their daily activity behaviours. However, no studies have examined how cognitive decline affects older adults’ activity behaviours within a 24-h framework. This study investigates the relationship between cognitive function and 24-h activity behaviours in older adults, further exploring whether these associations differ by sex.MethodThis study analyses data from the eighth wave of the Survey of Health, Ageing and Retirement in Europe, conducting a cross-sectional analysis of 814 older adults. Cognitive function was assessed using the SHARE-Cog tool, encompassing 10-word immediate recall, 10-word delayed recall, verbal fluency, and self-reported memory. 24-h activity behaviours (moderate-to-vigorous physical activity [MVPA], light physical activity [LPA], sedentary behaviour [SB], and sleep) were objectively measured with thigh-worn accelerometers. Compositional multivariate linear regression models were constructed using compositional data as the response variable, with cognitive function measures as predictors.ResultsHigher MVPA was linked to better cognitive outcomes (verbal fluency, 10-word immediate recall, and 10-word delayed recall) while SB and longer sleep related to poorer performance, with these associations being stronger in women (model p ≤ 0.001). Among women, cognitive outcomes were significantly associated with all activity behaviours (p range = 0.010–0.045). Women who self-reported poor memory and scored 0 on the verbal fluency spent approximately 45% of their day in SB, whereas those reporting excellent memory and scoring 60 spent 40.06% (37.18%, 42.86%) and 36.41% (31.53%, 41.10%) of their day sedentary, respectively. In contrast, men’s 24-h activity composition did not vary significantly with cognitive function (p range = 0.051–0.845).ConclusionOlder adults with better cognitive function tend to engage in more PA and reduce sedentary and sleep time. This relationship differed by sex, with females’ activity behaviours being more sensitive to cognitive function changes.ImplicationsThese findings suggest that interventions promoting healthy lifestyles in older adults should account for cognitive function, particularly in females.